PESANTREN TANPA PONDOK: STUDI KASUS PESANTREN MASYARAKAT OMAH NGAJI BERBAGI COLOMADU KARANGANYAR - Abror Dikna Anugrah; Mohamad Ali (PAI RAFAH, 2023)
Education can take place both inside and outside educational institutions and serves people of all ages. Pesantren is a religious institution that provides education and teaching as well as developing and spreading Islam. This study aims to describe the educational methods found in the Omah Ngaji Berbagi Community Islamic Boarding School by using pesantren education methods in the community. Researchers used a qualitative descriptive approach. Sources of data from the coaches, leaders, and students of the Omah Ngaji Berbagi Community Islamic Boarding School. Data analysis techniques in this study are data collection, data reduction, and conclusion drawing. The results of this study indicate that the Omah Ngaji Berbagi Community Islamic Boarding School is a pesantren that can accommodate people of all ages with the aim of fostering the community using pesantren education including learning to recite the Koran from scratch using the dirosa method, tahsin, basic Islamic material, Fiqh education (Kitab Safinatun Najah), memorization of the Quran & hadith, material on the chapter of Adab (Kitab Bulughul Maram). The material taught includes learning to recite the Koran from scratch for the first four months from the time of entry, tahsin, Fiqh material, memorization of the Quran & Hadith, adab, and Aqidah. The method of learning to recite from zero using books from Dirosa with twenty meetings, memorizing the Quran and hadith about tholabul ilmi, fiqh material taken from the book of Fikih Sakinah Tunnajah, and adab material using Kitab Bulughul Maram.